2001
DOI: 10.1128/jvi.75.5.2107-2118.2001
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Fever Virus Encephalitis: Properties of the Brain-Associated T-Cell Response during Virus Clearance in Normal and Gamma Interferon-Deficient Mice and Requirement for CD4+Lymphocytes

Abstract: Viral encephalitis caused by neuroadapted yellow fever 17D virus (PYF) was studied in parental and gamma interferon (IFN-␥)-deficient (IFN-␥

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 70 publications
2
71
0
3
Order By: Relevance
“…In our study, the vaccination induced the activation of CD8 + T cells, as could be observed on the significant increase of the CD8 + CD38 + T cells in all volunteers. CD4 + T cells are involved in several steps in the mechanics of immune response, as antibodies and cytokine production, among other events during the type-2 immune response, through B cells activation and posterior plasma cell differentiation (Mills et al 2000, Liu & Chambers 2001. As was observed in this study, all first-time vaccinees have presented a significant increase in their numbers of B cells (data not shown) and in the CD4 + T cell subsets.…”
Section: Discussionsupporting
confidence: 66%
“…In our study, the vaccination induced the activation of CD8 + T cells, as could be observed on the significant increase of the CD8 + CD38 + T cells in all volunteers. CD4 + T cells are involved in several steps in the mechanics of immune response, as antibodies and cytokine production, among other events during the type-2 immune response, through B cells activation and posterior plasma cell differentiation (Mills et al 2000, Liu & Chambers 2001. As was observed in this study, all first-time vaccinees have presented a significant increase in their numbers of B cells (data not shown) and in the CD4 + T cell subsets.…”
Section: Discussionsupporting
confidence: 66%
“…4). Similar immune cell infiltrates have been observed in hamsters and mice infected with YFV-17D, a neurovirulent DENV isolate, WNV and other neurotropic flaviviruses (Dominguez & Baruch, 1963;Hase et al, 1990;Klein et al, 2005;Liu & Chambers, 2001;Mateo et al, 2007;Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 52%
“…IFN-␥ has been implicated in control of some viral CNS infections (52-54), although it is not always essential (55). In a model of another flaviviral encephalitis, IFN-␥ deficiency was associated with impaired recruitment of inflammatory cells to the CNS and with increased viral titers, although no survival difference was noted (56). In the present study, we have shown: 1) IFN-␥-deficient animals are more susceptible to infection, 2) ␥␦ T cells produce IFN-␥ early following infection, and 3) this is one of their essential effector functions as cells from TCR␤ Ϫ/Ϫ IFN-␥ Ϫ/Ϫ mice were unable to transfer protection.…”
Section: Discussionmentioning
confidence: 99%